Pelatihan Pembuatan Video Pembelajaran Online Bagi Mahasiswa Calon Guru Pendidikan Agama Islam Sebagai Antisipasi Mewabahnya Covid 19 Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma’arif Bontang Tahun 2020/2021 - Muh Ikhsan (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2021)
Education is a central activity in advancing and developing the potential of students, which in this case are prospective students of Islamic religious education teachers at the Bontang Tarbiyah College of Sciences. With the outbreak of covid-19, educational activities have changed very significantly related to the implementation of learning activities from face to face to online learning. With these changes, it automatically forces education providers from basic to high levels to be able and creative in developing the online learning system. So that the results of online learning can be achieved properly, it is necessary to carry out training activities not only making learning videos but more importantly how a lecturer or teacher or student as a prospective teacher is able to use internet equipment such as using computers, using online learning tools, making online learning tools and the preparation of online learning materials and the process of implementing online learning. All of this is expected to produce the quality of education as expected.